The Architectural Decodification of Twin Towers: An Investigation into Cultural Communication and Related Symbolism Unrecognized by the Surrounding Community: The Architectural Decodification of Twin Towers: An Investigation into Cultural Communication and Related Symbolism Unrecognized by the Surrounding Community - An-Najwa, Rahilla; Fa'adihilah Tahnia, Talita (Universitas Islam Balitar, 2024)
The people of UIN Sunan Ampel Surabaya often hear the word